2016
DOI: 10.1038/srep38615
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic analysis of prenylated proteins in Plasmodium falciparum using an alkyne-modified isoprenoid analogue

Abstract: Severe malaria due to Plasmodium falciparum infection remains a serious threat to health worldwide and new therapeutic targets are highly desirable. Small molecule inhibitors of prenyl transferases, enzymes that catalyze the post-translational isoprenyl modifications of proteins, exhibit potent antimalarial activity. The antimalarial actions of prenyltransferase inhibitors indicate that protein prenylation is required for malaria parasite development. In this study, we used a chemical biology strategy to exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 57 publications
0
68
0
Order By: Relevance
“…Labeled proteins appear as bands in the fluorescence scan due to the conjugated fluorophore. Additionally, treatment with inhibitors of the isoprenoid biosynthesis such as lovastatin (Palsuledesai et al, 2016) and fosmidomycin (Suazo et al, 2016) are employed to reduce the pool of endogenous FPP and GGPP, thereby enhancing the incorporation of the isoprenoid probe to the prenylated proteins. This protocol describes metabolic labeling using the isoprenoid analogues C15AlkOH ( 2 ), C15AlkOPP ( 1 ), C15AlkMPP ( 4 ) and C15AlkOP ( 5 ) in COS-7 cells in the presence or absence of lovastatin.…”
Section: Basic Protocol 4: Metabolic Labeling Of Isoprenoid Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeled proteins appear as bands in the fluorescence scan due to the conjugated fluorophore. Additionally, treatment with inhibitors of the isoprenoid biosynthesis such as lovastatin (Palsuledesai et al, 2016) and fosmidomycin (Suazo et al, 2016) are employed to reduce the pool of endogenous FPP and GGPP, thereby enhancing the incorporation of the isoprenoid probe to the prenylated proteins. This protocol describes metabolic labeling using the isoprenoid analogues C15AlkOH ( 2 ), C15AlkOPP ( 1 ), C15AlkMPP ( 4 ) and C15AlkOP ( 5 ) in COS-7 cells in the presence or absence of lovastatin.…”
Section: Basic Protocol 4: Metabolic Labeling Of Isoprenoid Analoguesmentioning
confidence: 99%
“…The synthesis of C15AlkOPP ( 1 ) and its incorporation in vitro by protein farnesyltransferase was reported in 2007 (Hosokawa et al, 2007) followed by reports of its use in metabolic labeling in 2010 (DeGraw et al, 2010). Since that time, it has been employed for a variety of experiments including differential electrophoresis to study prenylation inhibitors (Palsuledesai, Ochocki, Markowski, & Distefano, 2014), labeling of proteins sensitive to human pathogens (Charron, Li, MacDonald, & Hang, 2013) and the delineation of the prenylome of Plasmodium falciparum , the causative agent of malaria (Gisselberg, Zhang, Elias, & Yeh, 2017; Suazo, Schaber, Palsuledesai, Odom John, & Distefano, 2016). Recently, it has been demonstrated that a-factor, a farnesylated pheromone from yeast retains full activity when the farnesyl group is substituted with several chemically modified isoprenoids used for metabolic labeling.…”
Section: Introductionmentioning
confidence: 99%
“… 16 20 Those compounds have proven useful for profiling prenylated proteins and also show great promise as tools to study how the levels of prenylated proteins vary in different disease models. 21 24 However, at present there is no information about the activity of proteins modified with such groups. Additionally, while in vitro enzymological experiments have provided convincing evidence that prenyltransferases can incorporate such analogs, 25 , 26 there are no reports concerning the ability of the two proteases or the methyltransferase to act on proteins containing these moieties to convert them to their fully processed state.…”
Section: Introductionmentioning
confidence: 99%
“…Similar expansions of potentially farnesylated proteins could be expected in pathogenic organisms that employ either endogenous or host-mediated farnesylation, such as Plasmodium falciparum, Candida albicans, and Legionella pneumophila. (75,(80)(81)(82)(83)(84)(85) Our expansion of the potential substrates recognized by FTase, supported by the reactivity of human-derived C(x)3X peptide sequences, highlights the importance of continuing studies towards identifying additional new and biologically relevant protein substrates and determining their prenylation state within the cell. In particular, identification and isolation of endogenously prenylated C(x)3X proteins will be essential to understanding the biological impact of prenylation of non-canonical FTase substrates.…”
Section: Discussionmentioning
confidence: 99%